2002
DOI: 10.5194/angeo-20-487-2002
|View full text |Cite
|
Sign up to set email alerts
|

HF radar polar patch formation revisited: summer and winter variations in dayside plasma structuring

Abstract: Abstract. Three intervals of polar patch formation, as observed by the CUTLASS Finland HF coherent radar, are presented. Simultaneous observations from a vertical ionosonde located at Longyearbyen on Svalbard, situated in the dayside convection throat region, allow for F-region plasma structuring, leading to polar cap patch formation to be determined. Solar wind and interplanetary magnetic field (IMF) pre-cursors of polar patch formation are investigated with MFI and SWE measurements from the Wind spacecraft. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
85
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(94 citation statements)
references
References 31 publications
8
85
1
Order By: Relevance
“…At high F-region altitudes the lifetime of the plasma is sufficiently long for the ionisation to be drawn through the polar region and into the nightside sector. During its transit through the polar cap the TOI may be modulated into polar patches and various processes have been proposed for this (for example Anderson et al, 1988;Sojka et al, 1993;Rodger et al, 1994;Milan et al, 2002). A modelling study by Bowline et al (1996) indicated that the TOI is expected to be prominent at Ny-Ålesund in the European sector in the evening under conditions of IMF B y negative, and observations of the remnants of the TOI and polar patches on the nightside in this sector are reported by Middleton et al (2008) and Pryse et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…At high F-region altitudes the lifetime of the plasma is sufficiently long for the ionisation to be drawn through the polar region and into the nightside sector. During its transit through the polar cap the TOI may be modulated into polar patches and various processes have been proposed for this (for example Anderson et al, 1988;Sojka et al, 1993;Rodger et al, 1994;Milan et al, 2002). A modelling study by Bowline et al (1996) indicated that the TOI is expected to be prominent at Ny-Ålesund in the European sector in the evening under conditions of IMF B y negative, and observations of the remnants of the TOI and polar patches on the nightside in this sector are reported by Middleton et al (2008) and Pryse et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…Localized enhancements in plasma density (100-1000 km in extent) known as polar patches have received even more attention than their low-density counterparts [Buchau et al, 1983;Weber et al, 1984;Rodger et al, 1994;Milan et al, 2002;Hosokawa et al, 2009;Dahlgren et al, 2012aDahlgren et al, , 2012bZhang et al, 2013;Burston et al, 2014;Goodwin et al, 2015]. A fundamental problem is what causes the plasma to be chopped into islands and what happens with patches after they have been separated from their source region including further structuring processes [Carlson, 2012].…”
Section: Introductionmentioning
confidence: 99%
“…Several observation techniques have been used for patch studies, such as direct electron density measurements by ionosonde (Buchau et al, 1983;Dandekar and Bullett, 1999;Dandekar, 2002), incoherent scatter radar (e.g. Valladares et al, 1994Valladares et al, , 1996Valladares et al, , 1998Carlson et al, 2002Carlson et al, , 2004Carlson et al, , 2006Lockwood and Carlson, 1992;Lockwood et al, 2005aLockwood et al, , 2005bOksavik et al, 2006a), and ionospheric tomography (Walker et al, 1999;Pryse et al, 2004), 630.0-nm airglow intensity that is proportional to electron density (Weber et al, 1984;Harris, 1995, 1996;McEwen et al, , 2004Lorentzen et al, 2004), and more indirectly by HF coherent scatter radars of the SuperDARN network (Rodger et al, 1994;Ogawa et al, 1998;Rodger and Graham, 1996;Milan et al, 2002Milan et al, , 2005Oksavik et al, 2006a). The latter technique does not provide a measurement of the electron density but gives the backscatter power from irregularities on electron density gradient associated E×B drift instability (Tsunoda, 1988;Chaturvedi and Ossakow, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…-IMF regulation of the cusp convection pattern causing alternating intake of high and low density plasma (Anderson et al, 1988;Rodger et al, 1994;Milan et al, 2002).…”
Section: Introductionmentioning
confidence: 99%